Understanding and Misunderstanding: an analysis of metonymy and metaphor in Croatian SMS text messages - Žic Fuchs, Milena (Array, 2007)
During the last twenty years we have witnessed an unbelievable spread of communication technologies, technologies which have produced extensive effects on various aspects of communication and also on languages. Apart from 'varieties' found on the Internet, SMS text messages have also evolved as a specific 'variety' in their own right. SMS text messages play an extremely important role within the framework of communication technologies in Croatia at present. A little over 4.5 million Croats use over 2.5 million mobile phones and the Croatian average of SMS text messages sent per month is 70, while the European average is 25 per month. Since SMS text messages have become a widespread and frequently used communication technology in Croatia, and since this technology has already influenced certain changes in the Croatian language, a corpus of over 3, 000 SMS text messages has been compiled over the past five years. The main focus of this paper is the analysis of the role that metonymy and metaphor play at what may at this point be broadly termed understanding and misunderstanding in SMS exchanges. A high degree of shared knowledge, as well as expected future communication largely determine the content and the overall linguistic output of SMS text messages, resulting in the extremely frequent appearance of shorthand forms of different kinds. Brevity, mainly induced by the technology itself is systematically achieved in a variety of ways. Metonymy and to a far lesser degree metaphor play a crucial role in achieving brevity specific to this 'variety'. The exceptionally frequent usage of metonymy in SMS text messages, and its often specific nature shed light primarily on the pragmatic role it plays in achieving understanding between participants in SMS exchanges. At the same time misunderstandings open up possibilities of viewing metonymy (as well as metaphor), not only in the pragmatic sense but also as providing insights into the still open questions in research on metonymy and metaphor. More precisely, analysis of the corpus helps us to further our understanding of the complementariness of cognitive and pragmatic perspectives of metonymy and metaphor, especially our understanding of knowledge organization and the notion of conventionality. Misunderstandings often occur when conventionality of metonymy (and metaphor) is not adhered to, that is when 'creativity' exceeds the usual bounds of shared knowledge. Thus the analysis provides not only insight into discourse-pragmatic conditions of metonymic use, but also insight into the constraints on the creation of metonymies and a variety of metonymical patterns which often lay behind misunderstandings. Special attention will be paid to contextual (one-time) metonymies and the way in which they further our understanding of conceptual structure and communicative relevance.